Day 1 - 1430 - Lisette Warren.pdf - Gill, Philip (Cranfield University, 2023)
Accounting for super-, plateau- and mesarate burning by lead and copper-based ballistic modifiers in double-base propellants: a computational study Lisette Warren - University of Edinburgh 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'